2005
DOI: 10.1007/s00125-004-1651-9
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone elicits long-term improvements in insulin sensitivity in patients with type 2 diabetes: comparisons with gliclazide-based regimens

Abstract: Aims/hypothesis: Recent studies have demonstrated that pioglitazone (PIO) has beneficial effects on insulin sensitivity compared with placebo in patients with type 2 diabetes. The effects of PIO and gliclazide (GLIC)-based therapy on insulin sensitivity have not previously been directly compared. This analysis aimed to compare the effects of 52 weeks of treatment with PIO (30-45 mg/day) and GLIC (80-320 mg/day), both titrated to maximum tolerable doses, as monotherapy or in combination with metformin (MET), on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Alternatively, pioglitazone might reduce the concentration of glucose in the blood to below a threshold at which insulin would be used. Finally, as previously suggested, pioglitazone could have a specific (β-cell sparing effect, manifest in other clinical studies by a reduction of circulating insulin, 15 and in animal studies by regranulation of the β cell. 16 We believe our results are generalisable to all patients with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 51%
“…Alternatively, pioglitazone might reduce the concentration of glucose in the blood to below a threshold at which insulin would be used. Finally, as previously suggested, pioglitazone could have a specific (β-cell sparing effect, manifest in other clinical studies by a reduction of circulating insulin, 15 and in animal studies by regranulation of the β cell. 16 We believe our results are generalisable to all patients with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 51%
“…However, there are several important differences in that study design and methods [24] when compared to our study. First, we believe that the small number of patients studied (n = 8) and short treatment duration (3 months) prevented the trend in weight gain (+0.9 kg) to become significant as it has been consistently reported with pioglitazone use by our group [21,22,33] and in the literature [9,34,35], in particular in studies lasting P6 months [11][12][13][14]16,36]. This is also true for other TZDs [9,10,15,37].…”
Section: Discussionmentioning
confidence: 71%
“…The mechanisms remain poorly understood. Weight gain most frequently develops within the first few months of treatment [11][12][13][14] and appears to plateau thereafter although there can be additional weight gain over time [15]. Occasionally, the use of thiazolidindiones is associated with lower extremity edema [15][16][17][18], although rarely with the development of congestive heart failure [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…For patients failing on sulfonylurea therapy, the addition of pioglitazone offered significantly greater improvements in HbA 1c and FPG than continued sulfonylurea therapy plus placebo () [46] and improvements in glycemic control that were comparable to the addition of metformin [47]. The addition of rosiglitazone to glibenclamide achieved significantly greater improvements in glycemic control than uptitration of the sulfonylurea alone [48].…”
Section: Glycemic Controlmentioning
confidence: 99%
“…Encouragingly, these improvements appear to be maintained during long-term therapy, despite some weight gain [19,61]. Charbonnel et al [47] directly compared the effects of pioglitazone and the sulfonylurea gliclazide on insulin sensitivity in type 2 diabetes. Using the homeostasis model of assessment (HOMA) to provide an indirect measure of insulin sensitivity (HOMA-IR), they found that over 1 year pioglitazone was associated with an improvement in insulin sensitivity, whereas gliclazide therapy was associated with a decrease.…”
Section: Insulin Resistancementioning
confidence: 99%